Burned forest area or dead tres? A discrete choice experiment for Catalan citizens - Farreras González, Verónica Inés (2012)
This paper estimates the social-welfare change due to the application of additional fire prevention measures on Mediterranean forests. The discrete choice experiment is applied to elicit the social preferences regarding fire prevention measures in terms of their impact on fire behaviour - fire propagation and intensity - and to estimate the value of these measures for the society. The results of the study show that additional fire prevention measures increase the welfare of the Catalan population and that fire propagation is the descriptor of fire behaviour that most concerns the population. This information may be used by policy makers and environmental managers to design their programmes and activities.